2018
DOI: 10.1177/1548051818760998
|View full text |Cite
|
Sign up to set email alerts
|

From Empowerment to Multilevel Creativity: The Role of Employee Self-Perceived Status and Feedback-Seeking Climate

Abstract: Employees' perception of their intrateam status plays an important role in the leader-member interaction process. Combining relational fairness theory and status theory, the present study reveals how leadership empowerment behavior (LEB) affects employee and team creativity. Specifically, we propose that LEB may increase employee creativity by elevating employee self-perceived status and enhance team creativity through fostering a feedback-seeking climate in the team. Moreover, we propose that, at the team lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Seibert et al (2004) stated that the practice of empowerment involves granting substantive decision-making powers to lower-level employees to perform work tasks and is manifested mainly as internal information sharing, work autonomy and responsibility. Scholars have revealed that stimulating employee creativity (Li et al, 2018), working ability (Eger et al, 2018) and innovative behavior (Liu et al, 2019) through empowerment is an effective means for enterprises to obtain response-ability and performance. However, several scholars have suggested that the effects of empowerment practice on employee behavior and organizational performance may not be as substantial as expected (Kaufman, 2015).…”
Section: Cms 154mentioning
confidence: 99%
See 2 more Smart Citations
“…Seibert et al (2004) stated that the practice of empowerment involves granting substantive decision-making powers to lower-level employees to perform work tasks and is manifested mainly as internal information sharing, work autonomy and responsibility. Scholars have revealed that stimulating employee creativity (Li et al, 2018), working ability (Eger et al, 2018) and innovative behavior (Liu et al, 2019) through empowerment is an effective means for enterprises to obtain response-ability and performance. However, several scholars have suggested that the effects of empowerment practice on employee behavior and organizational performance may not be as substantial as expected (Kaufman, 2015).…”
Section: Cms 154mentioning
confidence: 99%
“…EHRM, including development opportunities, workplace participation, enriched job design, information sharing and work-time control opportunities, is an effective way of stimulating the internal organization vitality (Van De Voorde et al, 2016). Scholars have revealed that EHRM could foster employee work engagement and innovative behavior (Liu et al, 2019), creativity (Li et al, 2018) and working ability (Eger et al, 2018), which were believed as positive factors improving firm performance (Gong et al, 2013). Other studies also gave a direct relationship between EHRM and firm performance.…”
Section: Big Data Enabling Empowerment-focused Human Resource Management and Platform Enterprise Innovation Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to Li et al (2018), creativity has an important role in tourism businesses; thus, leaders often seek to enhance it. Creativity can be defined as individuals' ability to create new ideas regarding products, services, and procedures (Roopak et al, 2019), which is the applied definition in this research.…”
Section: Creativitymentioning
confidence: 99%
“…Although there has been a large number of studies that examine the antecedents of creativity (Cheung & Wong, 2011; Dedahanov et al, 2016; Li et al, 2018); there is a paucity of research on the impact of the job embeddedness on creativity (Afsar & Badir, 2016; Karatepe, 2016). Therefore, this study aims to contribute to the study of job embeddedness on creativity in the tourism and hospitality industry through the lens of paternalistic leadership.…”
Section: Introductionmentioning
confidence: 99%